OVERVIEW OF VARIOUS DNA PROFILING TECHNIQUES USED IN FORENSICS - SHIWALI SHARMA,; VIDYA TALE, (International Journal of Pharma and Bio Sciences, 2016)
DNA fingerprinting, one of the great discoveries of the late 20th century, has revolutionized forensic investigations. The DNA molecule became the most powerful single tool in the multifaceted fight against crime. DNA analysis led to the exoneration of suspects and identification of victims of crimes, accidents and disasters. The review gives an outline of different and recent technologies in the field of forensic genetics, their evolution and emerging trends. Techniques like RFLP, PCR, STR, SNPs, MALDI-TOF MS have been explained, throwing a light in the field of human identification and population genetics. The collection and storage of the fingerprint profiles and DNA samples in the field of forensic science for nonviolent crimes is highly controversial. The legal, ethical and social issues surrounding the proliferation of DNA collection and storage are explored. A brief discussion on different technologies, overview of their applications, their merits and demerits, National and International scenario have been presented.